Idealitas Penguatan Kewenangan DPD RI dalam Perspektif Ketatanegaraan Indonesia yang Dinamis* - M Muslih (Wajah Hukum, 2019)
The Regional Representative Council is a new institution that replaces the Group and Regional Representatives as well as functions as a legislative member. However, the existence of this DPD has not been used optimally and is not "equalized" to the position of the DPR. When viewed from the perspective of democracy and popular sovereignty the electing process of DPD members is the same as that of DPR members through the LUBER and JURDIL Legislative Elections. Therefore, in order to optimize its role and function, the DPD needs to be strengthened with a variety of understandings and argumentations that support it.